2018
DOI: 10.21608/adjalexu.2018.57611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genistein and Oxaliplatin on Cancer Stem Cells in Oral Squamous Cell Carcinoma: An Experimental Study

Abstract: INTRODUCTION:Squamous cell carcinoma is one of the malignant diseases that affect the oral cavity worldwide. One of the theories regarding oral carcinogenesis is that tumor growth is dependent on cancer stem cells. Markers specific for these cells as CD44 have been investigated in hope of developing a deeper understanding for their role in carcinogenesis. Genistein, as chemopreventive agent, has been shown to suppress the growth of several tumors. Oxaliplatin is a chemotherapeutic compound that did show a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
2
1
Order By: Relevance
“…In accordance with the findings of this study, Mariadoss et al, (31) discovered that100% of the tumors had formed after 14 weeks of applying DMBA alone on the HBP. In contrast to the current study, Yang et al, (32) , Li et al, (33) and Hussein et al, (34) reported that OSCC induced by DMBA was seen in the examined HBPs was 53.5%,76.9% and 66.67% respectively. This discrepancy may be due to the using of different type of carcinogenic agent or technique or using old hamsters rather than the young ones.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with the findings of this study, Mariadoss et al, (31) discovered that100% of the tumors had formed after 14 weeks of applying DMBA alone on the HBP. In contrast to the current study, Yang et al, (32) , Li et al, (33) and Hussein et al, (34) reported that OSCC induced by DMBA was seen in the examined HBPs was 53.5%,76.9% and 66.67% respectively. This discrepancy may be due to the using of different type of carcinogenic agent or technique or using old hamsters rather than the young ones.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, IHC staining of GII showed positive membranous-cytoplasmic expression of CD44 (65.51%) that was seen throughout the epithelial layers and invading tumor cells, that showed highly significantly expression compared to GI (p value < 0.001). This result is in agreement with that of other investigators (34,35) . Paulis et al (2015) (35) concluded that, CD44 expression escalated the assaultiveness of tumor cells behavior.…”
Section: Discussionsupporting
confidence: 94%
“…These results did not differ much from (32,33) . This goes with the results of Hussein et al which concluded that oxaliplatin provides a curing role through the operation of oral carcinogenesis and may be employed as chemotherapeutic agent for carcinomas (34) . Further, Xu et al evinced that the oxaliplatin raised the apoptotic rate of human SCC, that designated a new target for the healing of oral neoplasms (35) .…”
Section: Discussionsupporting
confidence: 82%